Significant Skin Burns May Occur With The Use Of A Water Balloon In HIFU Treatment - Ritchie, R; Collin, J; Wu, F; Coussios, C; Leslie, T; Cranston, D (2012)
HIFU is a minimally-invasive therapy suitable for treating selected intra-abdominal tumors. Treatment is safe although skin burns may occur due to pre-focal heating. HIFU treatment of a renal transplant tumor located in the left lower abdomen was undertaken in our centre. Treatment was performed prone, requiring displacement of the abdominal wall away from the treatment field using a water balloon, constructed of natural rubber latex and filled with degassed water. Intra-operatively, ultrasound imaging and physical examination of the skin directly over the focal region was normal. Immediately post-operative, a full-thickness skin burn was evident at the periphery of the balloon location, outside the expected HIFU path. Three possibilities may account for this complication. Firstly, the water balloon may have acted as a lens, focusing the HIFU to a neo-focus off axis. Secondly, air bubbles may have been entrapped between the balloon and the skin, causing heating at the interface. Finally, heating of the isolated water within the balloon may have been sufficient to cause burning. In this case, the placement of a water balloon caused a significant skin burn. Care should be taken in their use as burns, situated off axis, may occur even if the overlying skin appears normal. © 2012 American Institute of Physics.